2001
DOI: 10.1542/peds.108.3.613
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Single Versus 3-Times-Daily Ferrous Sulfate Drops for Treatment of Anemia

Abstract: A single versus a 3-times-daily dose of ferrous sulfate drops over 2 months resulted in a similar rate of successful treatment of anemia, without side effects. To our knowledge, this is the first demonstration of the use of a single-dose daily regimen to treat anemia. Although not examined in the current study, use of a single-dose daily regimen may improve adherence to treatment of anemia in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 19 publications
5
44
2
11
Order By: Relevance
“…12 In this trial, a daily iron dose at the lower end of the recommended range (3 mg/kg of elemental iron) administered just once daily, at bedtime, and on an empty stomach was chosen. Two prior randomized clinical trials in children 10,11 informed this minimalist strategy aimed to en- Studies involving adults with IDA also support the use of low-dose oral iron treatment. In 1 trial, 14 octogenarians with anemia were randomized to 15 mg, 50 mg, or 150 mg of ferrous salts (gluconate or citrate) administered once daily and had virtually identical hematologic responses, but there were far less gastrointestinal toxic effects in the group receiving 15 mg. A study in women with iron deficiency using stable iron isotopes demonstrated that a single dose of iron engendered a prompt increase in serum hepcidin level that resulted in markedly reduced absorption of subsequent iron doses 12 hours or even 24 hours later.…”
Section: Discussionmentioning
confidence: 99%
“…12 In this trial, a daily iron dose at the lower end of the recommended range (3 mg/kg of elemental iron) administered just once daily, at bedtime, and on an empty stomach was chosen. Two prior randomized clinical trials in children 10,11 informed this minimalist strategy aimed to en- Studies involving adults with IDA also support the use of low-dose oral iron treatment. In 1 trial, 14 octogenarians with anemia were randomized to 15 mg, 50 mg, or 150 mg of ferrous salts (gluconate or citrate) administered once daily and had virtually identical hematologic responses, but there were far less gastrointestinal toxic effects in the group receiving 15 mg. A study in women with iron deficiency using stable iron isotopes demonstrated that a single dose of iron engendered a prompt increase in serum hepcidin level that resulted in markedly reduced absorption of subsequent iron doses 12 hours or even 24 hours later.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal for these studies was to evaluate the efficacy and acceptability of Sprinkles in controlled settings, and to describe the absorption of iron from Sprinkles. In collaboration with the Ghanaian Ministry of Health, Kintampo Health Research Centre, our first RCT demonstrated that in anemic infants, Sprinkles achieved a rate of cure similar to that of the reference standard, iron drops (6)(7)(8). Approximately 60% of infants went from an anemic to a non-anemic state in two months, which is a successful outcome in a malaria-endemic area.…”
Section: Evaluation Of Sprinklesmentioning
confidence: 83%
“…[29][30][31] Modified-release preparations of iron are licensed for once-daily dosage, but have no proven therapeutic advantage over conventional formulations. Contrary to some reports, 28 meta-analysis suggests that they are no better tolerated than standard formulations.…”
Section: Monitoring Of Responsementioning
confidence: 99%
“…28 Despite the lack of supportive meta-analytic data, 19 a dose reduction is sometimes effective and, because of the saturability of intestinal iron absorption, can be equally efficacious in replenishing iron stores. [29][30][31] Modified-release preparations of iron are licensed for once-daily dosage, but have no proven therapeutic advantage over conventional formulations. Contrary to some reports, 28 meta-analysis suggests that they are no better tolerated than standard formulations.…”
Section: Monitoring Of Responsementioning
confidence: 99%